Changes in the availability of human resources in health of Peru - John Barja-Ore; Natalia Valverde-Espinoza; Kiara Nathalie Fiestas Requena; Shirley Aguilar-Aguilar (Revista Cubana de Medicina Militar, 2021)
Introduction: Human resources are a fundamental element in the health system, their equitable distribution is essential to guarantee the attention of the health needs of a population. Objective: To describe the changes in the availability of human resources in health of the Ministry of Health and regional governments of Peru, during the 2017-2019 triennium. Methods: Non-experimental and retrospective study, based on secondary sources, which corresponded to the latest reports of the National Registry of Health Personnel of the Ministry of Health from 2017 to 2019. The availability of doctors, obstetricians and nurses who worked in health facilities, who correspond to different professions, according to the Peruvian regulatory framework. Absolute and relative frequencies were estimated. Results: The availability of doctors increased by 11.4%, obstetricians by 9.8% and nurses by 15.8%, from 2017 to 2019. In the first level of care, the availability of human resources in health is increased by 7.7%; Furthermore, in extreme poverty areas there was a 6.8% reduction in the number of doctors, a 4.4% increase in obstetricians in rural areas. Nurses were the fastest growing in the three natural regions of Peru. Conclusions: The availability of human resources in health increases for the year 2019 compared to 2017, in addition, nurses are the ones that present a greater percentage increase in this period.